Տայքի իշխանությունը հայ Բագրատունիների տերության համակարգում - Արման Եղիազարյան (ՀՀ ԳԱԱ հրատ.)
Во время господства арабов Тайк входил в административную единицу Третья Арминия наместничества Арминия Арабского халифата. В конце VIII в. граница Третьей Арминии сo Второй Арменией, куда входила область Великой Армении Гугарк, пролегала по линии соприкосновения Тайка и Гугарка. At the time of domination of the Arabs Taik was included in administrative unity of the Third Arminia of the Viceroyalty of Arminia of the Arabian Caliphate. At the end of the 8th century the boundary between the Third Arminia and the Second Armenia, which included region of Greater Armenia Gugark, was along splice line of regions Taik and Gugark.
Keywords: History; D History